Mężowie i żony, czyli uwag kilka o dwu „matrymonialnych” paszkwilach staropolskich z XVII stulecia (PDF 4,64 MB) (Książnica Śląska, 2025)
The article analyzes 17th century Polish poems about the matrimonialperipeties of Old Polish widows and widowers. The main charactersin the works are a man and a woman, whose archetypes were peopleof significant magnate families of the 17th century. It was noted thatthe same life situation (the loss of spouses and the desire to enter intoanother marriage) is presented differently. Pasquinade with a maleprotagonist is milder. On the contrary in lampoon about women asmain character, they are definitely humiliated and condemned, whichis related to the moral norms prevailing in the patriarchal society ofthe Polish-Lithuanian Commonwealth.